1993
DOI: 10.1055/s-2007-1023633
|View full text |Cite
|
Sign up to set email alerts
|

Stellenwert der Rezidivchirurgie in der Behandlung des Ovarialkarzinoms

Abstract: Recurrent ovarian cancer is still a significant problem despite intensive primary therapy, consisting of radical surgery and subsequent chemotherapy. The primary reason for consequent follow up investigations and immediate start of second-line therapy in cases of recurrence is based on the fact, that patients with relapse more than 12 months after primary therapy have a mean survival of 105 weeks after diagnosis. The value of surgical treatment is controversially discussed in the literature. Several authors ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Also, collectives in publications are probably similarly selected. In the published series, rates of complete resection between 9% and 82% and a share of inoperable patients with 12-45% are given (5)(6)(7)(8)(9)(11)(12)(13)(14)(15)(16)(17)(18) . Thus, the operative results of this study (45.9% of patients with complete tumor resection) appear in the upper middle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, collectives in publications are probably similarly selected. In the published series, rates of complete resection between 9% and 82% and a share of inoperable patients with 12-45% are given (5)(6)(7)(8)(9)(11)(12)(13)(14)(15)(16)(17)(18) . Thus, the operative results of this study (45.9% of patients with complete tumor resection) appear in the upper middle.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, for instance, showed that complete tumor resection alone correlates with longer survival (5,12,19) . Other authors reported that also at surgery for recurrence, patients could benefit from ''optimal debulking'' with residual tumors of up to 1 or 2 cm (6,7) . In the present study in which so far the largest series of surgeries for recurrence has been analyzed, the results of Eisenkop (5,19) were confirmed, and we found that only patients in whom complete tumor resection can be achieved benefit from surgery for recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der bereits erwähnte unreflektierte Einsatz von Tumormarkern in der Nachsorge, vor allem die Mehrfachbestimmung und die zu häufige Bestimmung, hat zu einer Diskussion darüber geführt, ob die regelmäßige Bestimmung von CA 125 im weiteren Verlauf nach Primärtherapie überhaupt gerechtfertigt ist [50,51]. Bevor diese Frage diskutiert wird, muß jedoch bedacht werden, daß die Rezidivdiagnostik mittels Tumormarker beim Ovarialkarzinom momentan deutlich besser ist als die zur Verfügung stehende Second-line-Therapie.…”
Section: Sinn Einer Tumormarkerbestimmung In Der Nachsorgeunclassified
“…Bevor diese Frage diskutiert wird, muß jedoch bedacht werden, daß die Rezidivdiagnostik mittels Tumormarker beim Ovarialkarzinom momentan deutlich besser ist als die zur Verfügung stehende Second-line-Therapie. Während Patientinnen mit Frühre-zidiv im Mittel lediglich 26 Wochen ab Rezidiv überleben, liegt dieser Zeitraum bei Patientinnen mit Spätrezidiv bei 105 Wochen [51]. Während Patientinnen mit Frühre-zidiv im Mittel lediglich 26 Wochen ab Rezidiv überleben, liegt dieser Zeitraum bei Patientinnen mit Spätrezidiv bei 105 Wochen [51].…”
Section: Sinn Einer Tumormarkerbestimmung In Der Nachsorgeunclassified